Pengaruh Komunikasi Persuasif Terhadap Pengetahuan Pasien Tuberkulosis Paru Di Puskesmas Kalirejo Kabupaten Pesawaran Tahun 2023 - Silfy Adelia; Lolita Sary; Dina Dwi Nuryani (Syntax Idea)
Pulmonary tuberculosis (TB) is one of the infectious diseases caused by Mycobacterium tuberculosis. The high incidence of Pulmonary TB is caused by the lack of knowledge of patients about Pulmonary TB and its transmission. It can be seen from the incidence of Pulmonary TB at the Kalirejo Health Center, Pesawaran Regency, has increased every year. In 2020 (51) cases, in 2021 (58) cases and in 2022 (61) cases. The purpose of this study was to determine the effect of linear communication, interactional communication and transactional communication on the knowledge of Pulmonary TB patients. This quantitative study was conducted in September 2023-January 2024 at the Kalirejo Health Center, Pesawaran Regency with a quasi research design experimental. The population is Pulmonary TB patients at the Kalirejo Health Center, Pesawaran Regency in 2023 with a sample of 40 people. Data were analyzed using the Krusskal-Wallis test. The results showed that there were differences in knowledge of Pulmonary TB patients before and after linear communication was given by 5.26 (p value 0.023), interactional 11.9 (p value 0.010) and transactional 15.84 (p value 0.007). This shows that the communication intervention that has the most influence on the influence of persuasive communication in pulmonary TB patients is transactional communication. Pulmonary TB control personnel need to implement transactional communication methods as one of the health promotion strategies to increase knowledge.